Sub-Terahertz: generation and detection - Othman, Mohd Azlishah (2013)
Nowadays, there has been an increasing interest in Terahertz (THz) radiation for application across scientific disciplines including atmospheric sensing, medical diagnosis, security screening and explosive detection. The limitation of THz generators and detectors has gained interest from scientists and engineers to explore the development of both sources and detectors. With the advantages of low cost, low power consumption, high reliability and potential for large-scale integration, sub-THz generator and detector can be developed using CMOS process technology.